USE OF LOCAL ANESTHESIA AS PREPARATION FOR INTRAVENOUS ACCESS IN EMERGENCY DEPARTMENT: LITERATURE REVIEW - Farida Zahra Khairun Nisa; Hikmat Pramajati; Imam Tri Sutrisno; Subhan Manggala Putra; Elissa Noorwillah Islami (LPPM Universitas An Nuur, 2026)
Background; Venipuncture is a common procedure in the Emergency Department, with significant pain reported in both children and adults. One pain management option is the use of local anesthetics before the procedure. This study aims to determine the effectiveness of local anesthetics in reducing pain after venous injections based on the literature. Method; A search was conducted in PubMed, ScienceDirect, Scopus, Springer, and SageJournal using predetermined keywords. Study screening was carried out in stages according to the prism flow. After filtering, five literatures were obtained. Result; The analysis results showed that coldspray, cryospray, vapocoolant spray, and buzzy were effective in reducing pain and suitable for use in the Emergency Department. In contrast, topical ketamine and EMLA, although they significantly reduced pain levels, their slow onset time makes them unsuitable for use in the Emergency Department. Conclusion; In conclusion, several local anesthetics can be appropriate for emergency conditions, supported by patient perceptions that local anesthetic intervention is performed before invasive procedures.